Pengawetan Ikan Tongkol Menggunakan Abu Pelepah Kelapa Sebagai Alternatif Pengawet Alami - Ruka Yulia; Rita Sunartaty (Fakultas Teknik, 2022)
Coconut fronds are agricultural wastes that are abundant in Aceh Province. Coconut midrib which is processed into ash has great potential to be used as a natural preservative. Preservation of tuna using coconut frond ash is a breakthrough from the natural resources of Aceh's local wisdom. The purpose of this study was to determine the protein content, fat content and calcium content of mackerel fish preserved with coconut frond ash. The experimental design used was a completely randomized design with 2 variables and 3 replications. The research variables used were the amount of coconut frond ash and the drying time of tuna. The amount of midrib ash used was 3, 6 and 9 grams and the drying time was 10, 15 and 20 hours in sunlight. The results showed that the amount of ash and drying time had a significant effect on water content and protein content. While the treatment and drying time had no significant effect on the fat content.